Mitigation of the alkali-aggregate reaction against the addition of sugarcane berry ash - Vitor da Silva Macedo, José; Inojosa Lyra, Bernardo; Cristina Barreto Monteiro, Eliana; Just da Costa e Silva, Angelo; Wanderley Correia de Oliveira Andrade, Tibério (Seven Editora, 2023)
The alkali-aggregate reaction (RAA) is a pathological manifestation caused by the chemical reaction between the reactive minerals of the aggregates and the alkaline oxides of sodium and/or potassium (Na2O and K2O, respectively), derived essentially from cement, forming a gel that in the presence of water expands inside the concrete or mortar. The expansion of this gel, which is deposited in the pores of the structure, can generate cracks, displacements, and may lead to the rupture of the structure if the tension reaches a level in which the concrete or mortar does not resist (Poole, 1992; Figuerôa and Andrade, 2007; Fernandes and Broekmas, 2013). DOI: https://doi.org/10.56238/tfisdwv1-032